PERANAN DALAM PROSES PEMBANGUNAN BERKELANJUTAN DALAM PERENCANAAN PEMBANGUNAN NASIONAL - I Kadek Donny Wishanesta; Ni Made Widani (Sekolah Tinggi Pariwisata Mataram, 2023)
The purpose of this study is to determine the concept of sustainable development and its principles. To develop a development plan based on the concept of sustainable development, it is necessary to understand what elements are needed as well as what factors and tools are needed to develop sustainably. The pillars of sustainable development are economic sustainable, socially sustainable and environmentally sustainable, all of which must develop in a balanced manner; otherwise development will be trapped in conventional development models that emphasize economic growth alone and leave social and environmental development behind. In addition, for the success of sustainable development, the need for social capital that is able to maintain good cooperative relations between various government agencies both internal and external, as well as synergy between the government, private sector and the community with a multi-party approach from the three groups. in the preparation of environmentally sound development plans and policies